Apple in the middle - Quigley, Dawn (Contemporary voice of indigenous peoples series, 2020)
A biracial girl, Apple, rejected her Native American ancestry after suffering a racist epithet, but can't seem to be accepted by either the white or Native cultures. One summer, her father sends her to spend time on the Turtle Mountain Indian Reservation to engage with her Native American relatives. Reluctantly, she tries to find a connection, especially to her dead mother, and in the process of learning more about her heritage, learns to take pride in where she came from. Additionally, she has to contend with an angry Indian man who dated Apple's mother in high school and is furious at her for marrying a white man. He decides to turn his rage and vengeance on her daughter.